The Effect of Special Exercises According to Kolb Model On Learning Dribbling In Handball for Female Students - Saleem, Sauzan; Deyaa, Noor (Journal of Physical Education, 2019)
The Effect of Special Exercises According to Kolb Model On Learning Dribbling In Handball for Female Students The importance of the research lies in using Kolb learning style in learning handball dribbling. The researcher prepared special exercises according to Kolb learning style as well as according to the traditional learning style. These exercises were applied to the research sample consisting of experimental groups (B / 22) and controlled group (D / 10). The aim of the research is to identify the differences between the pretest and posttest test in dribbling. There were significant differences between the pretest and posttest and in favor of the posttests in handball dribbling. The researcher concluded that Kolb method of learning have a positive effect on learning dribbling in handball. Finally the researchers recommended using different teaching methods. Keywords: dribbling, Kolb learning style, handball.